Prevalence of HTN and its risk factors among tribal population in Chhattisgarh (India) as per the fifth round of the National Family Health Survey - Tripti Nagaria; Neha Singh; Madhur Verma; Angad Singh; Kamlesh Jain; Nirmal Verma; Monika Dengani; Shailendra Agrawal; Sukhbir Singh; Sonu Goel (PLoS ONE, 2025)
Background The so-called protected tribal population also faces the burden of non-communicable diseases (NCDs). The high-altitude tribes are thought to be genetically and environmentally protected from hypertension-like diseases. Methods Survey of the National Family Health Survey-5 (2019-2022) employs a two-stage sampling method (PSU). The total population of 72010, aged 15 years and above, were included from Chhattisgarh, India, out of which 27760 belong to tribes. Pre-hypertension (pre-HTN) and hypertension (HTN) were measured using standard procedures. Results Overall prevalence of pre-HTN and HTN (42.7% and 26%) in tribes was comparable to the general population (43.14% and 25.48%). The prevalence of pre-HTN was higher than HTN in tribes. We observed a positive association between increasing age and prevalence of HTN in males and females. aOR ratio (12.58; 9.72 -16.28) among the females aged 65-74 years was the highest, and the aOR (9.63; 6.89 -13.44) ratio among the males was recorded highest at 75 years and above. Odds of developing HTN increased with higher education (aOR 1.24; 1 -1.53 and 0.69; 0.5 -0.94), highest wealth index (aOR 1.38; 1.04 -1.83 and 1.35; 1.01 -1.8) in male and females respectively. Conclusion The elevated frequencies of HTN among tribes against their background condition confirm that their epidemiological transition is loaded with significant HTN. We recommend sharing this initiative with our primary healthcare providers and to the policymakers to take corrective measures because they serve as the first point of contact for early screening to reduce the burden of illness.